A Coherent Method to Fit Cultural Anthropology into the Fertility Study - Subedi, Pushp Kamal (Tribhuvan University Journal, 2010)
This paper argues for a new analytical framework that draws the most attention to the relationship between demography and sociocultural anthropology, involving micro-level research. It is called ‘a case study approach to studying fertility’, which involves ‘process and product’. The analysis process constitutes a specific way of gathering comprehensive, systematic, and in-depth information about fertility, which leads eventually to a product: a case study fertility data. The incorporation of theories of culture as ‘the evaluative behaviour of social actors’ and ‘social constructionism’ appears to provide an attractive alternative theory of culture for fertility analysis. Special emphasis is placed on the political, economic, feminism, and social constructionism or, more generally, practice approaches to social facts. The present paper begins with good reason to think why we use a case study approach to studying fertility and its theoretical base. We then reconnoitre ‘a theory of culture for demography’ in order to flesh out ‘a coherent method to fit cultural anthropology into the demographic enterprise: a third generation fertility study’. Such interrogation helps clarify problems and advantages in terms of theory, methodology, practicality, useful outcomes and differences. Key words: Demography and sociocultural anthropology; fertility Tribhuvan University Journal Volume XXVI No. 1, 2009 Page: 69-80